Study of near‐symmetric cyclodextrins by compressed sensing 2D NMR. (4th January 2013) - Misiak, Maria; Koźmiński, Wiktor; Chmurski, Kazimierz; Kazimierczuk, Krzysztof
<x xml:space="preserve">Abstract</x> The compressed sensing NMR (CS‐NMR) is an approach to processing of nonuniformly sampled NMR data. Its idea is to introduce minimal lp‐norm (0 < p ≤ 1) constraint to a penalty function used in a reconstruction algorithm. Here, we demonstrate that 2D CS‐NMR spectra allow the full spectral assignment of near‐symmetric β‐cyclodextrin derivatives (mono‐modified at the C6 position). The application of CS‐NMR ensures experimental time saving and the resolution improvement, necessary because of very low chemical shift dispersion. In the overnight experimental time, the set of properly resolved 2D NMR spectra required for the unambiguous assignment of mono(6‐deoxy‐6‐(1‐1, 2, 3‐triazo‐4‐yl)‐1‐propane‐3‐O‐(phenyl)) β‐cyclodextrin was obtained. The highly resolved HSQC spectrum was reconstructed from 5.12% of the data. Moreover, reconstructed 2D HSQC–TOCSY spectrum yielded information about the correlations within one sugar unit, and 2D HSQC–NOESY technique allowed the sequential assignment of the glucosidic units. Copyright © 2013 John Wiley & Sons, Ltd.